2022
DOI: 10.1101/2022.01.18.22269349
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-Term Persistence of IgG Antibodies in recovered COVID-19 individuals at 18 months and the impact of two-dose BNT162b2 (Pfizer-BioNTech) mRNA vaccination on the antibody response

Abstract: This era of emerging variants needs a thorough evaluation of data on the long-term efficacy of immune responses in vaccinated as well as recovered individuals, to understand the overall evolution of the pandemic. In this study, we aimed to assess the dynamics of IgG titers over 18 months in 34 patients from the Umbria region in Italy, who had a documented history of COVID-19 infection in March 2020, and then compared the impact of two-dose BNT162b2 (Pfizer-BioNTech) vaccination on the antibody titers of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In cases where antibodies can be measured quantitatively, it may also be possible to use them to assess the level of protection in a population, although there is currently no consensus on antibody-based correlates of protection for SARS-CoV-2 [4]. While antibodies persist in most infected individuals for up to a year (with early evidence pointing at up to 18 months) [54][55][56][57] the reinfection risk with the immune-escaping Omicron variant, is reported to be much higher than in previous VOCs in both vaccinated and previously infected individuals, indicating that the presence of antibodies is less indicative of a level of protection against infection. However, seroprevalence estimates remain indicative of protection against severe disease and death, as cellular immunity is unlikely to be disrupted even with an immune escaping VOCs.…”
Section: Implications and Next Stepsmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases where antibodies can be measured quantitatively, it may also be possible to use them to assess the level of protection in a population, although there is currently no consensus on antibody-based correlates of protection for SARS-CoV-2 [4]. While antibodies persist in most infected individuals for up to a year (with early evidence pointing at up to 18 months) [54][55][56][57] the reinfection risk with the immune-escaping Omicron variant, is reported to be much higher than in previous VOCs in both vaccinated and previously infected individuals, indicating that the presence of antibodies is less indicative of a level of protection against infection. However, seroprevalence estimates remain indicative of protection against severe disease and death, as cellular immunity is unlikely to be disrupted even with an immune escaping VOCs.…”
Section: Implications and Next Stepsmentioning
confidence: 99%
“…*Unity Studies Collaborator Group: Ximena Aguilera19 , Sheikh Al-Shoteri20 , Eman A Aly8 , Mauricio Apablaza 21 , Rosemary A Audu22 , Amal Barakat8,23 , Abdulla S Bin-Ghouth24 , Enyew Birru25 , Dejan Bokonjic 26 , Shelly Bolotin27,28 , Henry K Bosa29,30 , Emily L Boucher31 , Elma Catovic-Baralija32 , Alexei Ceban33 , Annie Chauma-Mwale34 , Judy Chen35 , Battogtokh Chimeddorj 36 , Pui Shan Chung 10 , Cheryl Cohen 37 , Tienhan S Dabakuyo-Yonli38 , Gabriel R Deveaux31 , Boly Diop39 , Titus H Divala40 , Emily K Dokubo41 , Irene O Donkor42 , Claire Donnici 31 , Nathan Duarte43 , Natalie A Duarte44 , Timothy G Evans7,14 , Lee Fairlie45 , Ousmane Faye46 , Gudrun S Freidl11 , Claudia González19 , Tiffany G Harris47,48 , Belinda L Herring 3 , Sopon Iamsirithaworn49 , Gloria Icaza 50 , Rhoda Ila 51 , Natasha Ilincic44 , Elsie A Ilori52 , Francis Y Inbanathan 9 , Vicki Indenbaum53 , John Kaldor54 , Dayoung Kim31 , Olatunji M Kolawole55 , Jambo C Kondwani56,57 , Tatiana Kuchuk 58 , Pritesh J Lalwani…”
mentioning
confidence: 99%
“…Most studies agree that there was no significant increase in cellular immunity [180], circulating antibodies, neutralizing titers, or antigen-specific memory B cells in recovered subjects after the second vaccine dose [150,[181][182][183]. When present, this increase was characterized by the rapid decay of the antibody titer [151], concurrent with a greater occurrence of the related adverse events. Also in one of the previously reported systematic reviews [132] it was observed that vaccination in subjects recovered from COVID-19 provides modest protection from reinfection (RR = 1.82 [95% CI 1.21-2.73], P = 0.004) with an extremely marginal difference in absolute risk (RA = 0.004 person-years [95% CI 0.001-0.007], P = 0.02); at the same time, adverse events after vaccine injection were more frequent after the second dose (mean: 0.95 vs 1, 91) in healed subjects compared to the COVID-19--naïve ones (mean: 1.63 vs 2.35).…”
Section: The Role Of Hybrid Immunitymentioning
confidence: 98%
“…Moreover, it was clearly shown that the BNT162b2 mRNA vaccination elicits a strong systemic immune response by drastically increasing the development of neutralizing antibodies in the serum, but not in the saliva, thus failing to limit the acquisition of the virus upon its entry [149]. The persistence and the neutralizing capacity of the specific antibodies in healed patients with lasting protection was recorded in several longitudinal studies (12 months in the study by Hwang et al [150]; 13, 14, 18 months in the studies by Gallais et al [144], Eyran et al [148] and Dehgani-Morabaki et al [151].…”
Section: Comparisons Between Vaccinated and Unvaccinated In The Devel...mentioning
confidence: 99%
“…IgM antibodies are usually detected before IgG but decline more rapidly. IgG persists for more than 12 months [ 4 , 5 ], and in some cases for 18 months [ 6 , 7 ] after past COVID-19 infection. The precise duration for the detection of IgG is unknown, but it is assumed that the antibodies give some level of immunity for at least a year [ 5 ].…”
Section: Introductionmentioning
confidence: 99%